DETERMINANT FACTOR OF DEPRESSION IN RURAL ADOLESCENT: A LITERATURE REVIEW - Mohammad Wavy Azkiya; R Endro Sulistyono; Mashuri Mashuri; Primasari Mahardhika Rahmawati (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Adolescence is a period of transition from childhood to adulthood. This stage of development is a transitional period of self-discovery marked by physical, emotional, and psychological changes. However, young people are often faced with poverty, sexual abuse, or violence, making teens vulnerable to mental health problems. Adolescents who live in rural areas are likely to be more susceptible to mental health problems because rural areas have a high degree of social intimacy, and the economic focus is on the agricultural sector. So, the psychological pressure on adolescents in rural areas will be heavier, and if the coping mechanism is not suitable, these adolescents will be more susceptible to depression. Objective: This study aims at reviewing and synthesizing the determinants factor of depression among adolescent in rural area. Design: This study design was a systematic review using the PICO framework. Data Sources: This data was carried out since June 2021 from various journal databases in the last five years (2017-2021), including ScienceDirect, PubMed, and Taylor & Francis. The keywords combined with Boolean operators (“AND” and “OR”) to find literatures, namely "Factor" OR “Risk Factor” AND “Depression” OR “Depressive” OR “Depress” AND “Adolescent” OR “Teens” AND “Rural”. 13 articles meet the inclusion criteria and meet the qualifications for review. Review Methods: A systematic procedure is used to collect articles, as well as a critical appraisal and data synthesis with qualitative synthesis. Results: Based on a review of several articles, factors that can influence the occurrence of depression in rural adolescents include discrimination, adverse childhood experiences, victimization, socioeconomic migration of parents, family, cellphone addiction, postpartum pregnancy, and gender in adolescents. Conclusion: Overall, these factors can cause psychological pressure and due to poor coping mechanisms resulting in depression in adolescents in rural areas.